Autonomous motivation promotes goal attainment through the conscious investment of effort, but mental contrasting with implementation intentions makes goal striving easier - Riddell, Hugh; Lamont, Wesley; Lombard, Merrill; Paduano, S.; Maltagliati, S.; Gucciardi, Daniel F.; Ntoumanis, Nikos (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2024)
People with autonomous motives (e.g., personal importance) may use automated strategies to effortlessly sustain goal-directed behavior and overcome obstacles. We investigated whether conscious effort, ease of goal striving, physiological effort, and the number of obstacles encountered mediate relations between motives and goal attainment for a competitive cycling goal. Additionally, half the participants (n = 57) were trained in Mental Contrasting with Implementation Intentions (MCII)–a technique that facilitates development of goal-directed behavior–with remaining participants (n = 54) treated as controls. Conscious investment of effort mediated relations between autonomous motives and goal attainment. Subjective ease of goal striving and physiological effort did not. This result indicates that successful goal striving is not perceived as effortless for autonomously motivated individuals working on competitive goals. Conversely, MCII predicted a reduction in obstacles, which in turn was associated with easier goal striving but not goal attainment. Although MCII did not support goal attainment in the current study, its ability to minimize the influence of obstacles may still be useful for other types of goals or for sustaining long-term goal pursuit.